PARTISIPASI PEMILIH DISABILITAS PADA PENYELENGGARAAN PEMILIHAN UMUM DI KOTA SEMARANG (Studi Komparasi Pemilihan Umum 2019 dan 2024) - Fauzan Haidar Ramadan; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
This study analyzes the participation of voters with disabilities in the general elections in Semarang City through a comparative study between the 2019 and 2024 elections. The research examines how participation changed between two election cycles and what factors influenced these changes. Employing an exploratory qualitative method with in-depth interviews of twelve informants—including a KPU Semarang Commissioner, PPUA Disabilitas representatives, Sahabat Difabel Community, SLBN Semarang, and voters with three disability types (physical, visual, hearing-speech impairments) the study finds that participation increased from 32% in 2019 to 41.6% in 2024, with patterns shifting from passive-reactive to semi-independent. However, this improvement was asymmetrical: blind voters and urban flatland zones recorded the highest gains, while deaf-mute voters and coastal hill zones experienced minimal change. Participation is influenced by general factors (physical TPS accessibility, assistive device quality, KPPS capacity, communication barriers, inclusive socialization, family support, political efficacy, economic costs, social stigma) and Semarang specific factors (tidal flooding, hilly topography, suburban underreporting, organized disability communities, progressive KPU). The study concludes that Semarang City is situated between the consolidation-implementation and substantive-transformative phases of the inclusive democracy spectrum.